2016
DOI: 10.1088/1748-0221/11/12/p12020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of de-noising methods to improve the precision of the ILSF BPM electronic readout system

Abstract: In order to have optimum operation and precise control system at particle accelerators, it is required to measure the beam position with the precision of sub-µm. We developed a BPM electronic readout system at Iranian Light Source Facility and it has been experimentally tested at ALBA accelerator facility. The results show the precision of 0.54 µm in beam position measurements. To improve the precision of this beam position monitoring system to sub-µm level, we have studied different de-noising methods such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…A regression analysis was applied to the retrieved data from satellite and ground- temperature. These results are in good agreement with the literature (Almazroui et al, 2012;Namdari et al, 2018;Shafiee et al, 2016aShafiee et al, , 2016bSingh and Oh, 2007). Previous studies indicated that any increase in ambient air temperature causes a reduction in relative humidity, leading to a decrease in threshold wind speed to initiate dust emissions.…”
Section: Sand and Dust Storm And Severe Sand And Dust Storm Occurrences In Shalamchehsupporting
confidence: 92%
“…A regression analysis was applied to the retrieved data from satellite and ground- temperature. These results are in good agreement with the literature (Almazroui et al, 2012;Namdari et al, 2018;Shafiee et al, 2016aShafiee et al, , 2016bSingh and Oh, 2007). Previous studies indicated that any increase in ambient air temperature causes a reduction in relative humidity, leading to a decrease in threshold wind speed to initiate dust emissions.…”
Section: Sand and Dust Storm And Severe Sand And Dust Storm Occurrences In Shalamchehsupporting
confidence: 92%
“…6. To remove this noise, we implemented a Symlets 4 wavelet filter in Matlab (Chavan et al 2011;Shafiee et al 2016) as shown by the reddish line in Fig. 5.…”
Section: Sipm Signal Experimental Resultsmentioning
confidence: 99%
“…The denoising process consists of applying the wavelet decomposition to the raw data, thresholding the wavelet coefficients based on a set of rules, and applying the inverse wavelet transformation. The optimization of wavelet-based denoising requires a choice of mother wavelet and its scale as well as the threshold for the wavelet coefficients [17]. Table 1 lists the set of mother wavelets (including their various order and coefficient numbers) that were explored in this work.…”
Section: Traditional Denoising Methodsmentioning
confidence: 99%